Has public support for solidarity in healthcare financing in the Netherlands changed over time? A repeated cross-sectional study. (May 2023) - Meijer, Marloes A.; Brabers, Anne E.M.; de Jong, Judith D.
Highlights: Own willingness to contribute increased over time, but not in all subgroups Expected willingness to contribute did not change among the general population Public support for solidarity in healthcare financing is not in decline A majority of the Dutch population remains willing to share healthcare costs The principles of the solidarity-based healthcare system are found to be supported Abstract: It is argued that solidarity-based healthcare systems are under pressure and that public support is decreasing. It can, therefore, be expected that support for solidarity in healthcare financing has diminished over time. However, little research has been conducted into this. To fill this gap, we used survey data from 2013, 2015, 2017, 2019, and 2021 to examine changes in public support for solidarity in healthcare financing in the Netherlands over time. This was operationalised as the own willingness and the expected willingness of others to contribute to other people's healthcare costs. Using logistic regression analysis, we found that the own willingness to contribute has slightly increased among the general population over time, although this was not observed in all subgroups. No change in the expected willingness of others to contribute was observed. Our results suggest that the willingness to contribute to other people's healthcare costs has, at least, not decreased over time. A majority of the Dutch population remains willing to share the burden of healthcare costs, indicating support for the principles of the solidarity-based healthcare system. However, not all people are willing to contribute to the healthcare costs of others. In addition, we do not know how much people want to pay. Further research into these topics is necessary.